2001
DOI: 10.1002/ana.1285.abs
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of sporadic Creutzfeldt‐Jakob disease on the island of Crete associated with a high rate of PRNP 129‐methionine homozygosity in the local population

Abstract: Since the spring of 1997, when the Neurology Department of the University Hospital of Crete admitted its first patient, nine cases (eight neuropathologically confirmed and one probable) of sporadic Creutzfeldt-Jakob disease (sCJD) have been recorded. This represents an annual incidence five-fold higher than expected based on the island's population (0.54 million). Molecular analysis of the prion-protein gene (PRNP) showed no mutations in any of the seven CJD cases studied. Five patients (ages 64-88 years) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…The observation may reflect the higher incidence of the Met allele in the population, since 54% of the population in Crete are homozygous for Met [21]. Homozygosity of Met on codon 129 has been reported to be a predisposing factor also for sCJD [29].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The observation may reflect the higher incidence of the Met allele in the population, since 54% of the population in Crete are homozygous for Met [21]. Homozygosity of Met on codon 129 has been reported to be a predisposing factor also for sCJD [29].…”
Section: Discussionmentioning
confidence: 92%
“…This putative East-West gradient seems to be confirmed by our analysis. Not only have Japan and Turkey a higher Met-allele prevalence than Denmark, also countries in the Eastern part of Europe like Greece, Finland, Poland and Slovakia [19][20][21][22][23] tend to exhibit a higher occurrence of the Met allele than countries situated in the Western part i.e. France, UK, Iceland, Austria and Denmark [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…If the heterozygotes have a lower probability to develop CJD, then the native Americans will be less susceptible than other populations as they have the highest rate of heterozygotes M/V (46.9%). And according a recent study, where a high frequency of M homozygotes in Crete island was associated with an increased number of sporadic CJD patients [Plaitakis et al, 2001], the high frequency observed in CE Asia (88.1%) for Met homozygotes could result in a very high risk for prion diseases in that group. Variation at the codon 129 (and thus, variation in the whole PRNP) is highly structured by continent as shown from AMOVA results, suggesting that natural selection may have acted as a diversification factor among human groups.…”
Section: Discussionmentioning
confidence: 98%
“…[7]. Clear differences in the distribution of this genetic trait exist between Europeans and Asian populations [8][9][10][11][12][13][14][15][16][17][18][19][20]. In the present work we estimated the distribution of M129V in a Brazilian population and compared genotype and allele frequencies with previously published data.…”
mentioning
confidence: 98%